2023
DOI: 10.1002/smll.202206528
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Roughness Enhanced Gel/Elastomer Interfacial Bonding Enables Robust and Stretchable Triboelectric Nanogenerator for Reliable Energy Harvesting

Abstract: characteristics enable it to be a promising candidate for powering IoTs. [9][10][11][12][13][14][15] In particular, TENG is expected to be a soft and stretchable device which is highly integrated with human body and motion for powering upcoming era of wearable electronics. The structure of TENG consists of a pair of triboelectrification materials with distinct charge affinities and corresponding back electrodes, which exploits the coupling effect of triboelectrification and electrostatic induction. [16,17] Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Different levels and types of deformation are inevitable in the operation of stretchable devices, which requires robust interfaces to withstand deformation and maintain a stable performance of any sensor. [ 24 ] The bonding strength between two commercial silicone rubbers (PDMS and Ecoflex) and an optimal mix (a PDMS:Ecoflex mixture at a mass ratio of 1:10, Figure S11, termed “P–E”) to the ferroelectric ceramic was therefore evaluated in detail. Figure a shows the tensile stress–strain curves of the peel tests for these composite structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different levels and types of deformation are inevitable in the operation of stretchable devices, which requires robust interfaces to withstand deformation and maintain a stable performance of any sensor. [ 24 ] The bonding strength between two commercial silicone rubbers (PDMS and Ecoflex) and an optimal mix (a PDMS:Ecoflex mixture at a mass ratio of 1:10, Figure S11, termed “P–E”) to the ferroelectric ceramic was therefore evaluated in detail. Figure a shows the tensile stress–strain curves of the peel tests for these composite structures.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] Since silicone polymers are chemically inert and hierarchical ceramics have interconnected channels with open porosity, mechanical interlocking is considered to be the key factor in determining the interface strength. [ 24,26a ] In terms of classical adhesion theory, the process of mechanical interlocking proposes that adhesion results from polymer penetration into the troughs and pores of a rough substrate. [ 28 ] In order to achieve interlocking, the polymer must exhibit good wettability and fluidity to spread on the ceramic surface and fully penetrate into the pores.…”
Section: Resultsmentioning
confidence: 99%
“…Gels are composed of a 3D framework and swelling liquid, which are stretchable and can be designed with high dielectric constant. Such properties enable gels as ideal fillers for stretchable dielectric materials because these properties can avoid an annoying stiffness problem in rigid fillers and enhance the ε r of composites synchronously. In the introduction of this work, gels were prepared with high softness and dielectric constant for doping elastomers, as shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In our previous studies, Carbonate-gels were found to be very adhesive. 26,39 Their interfacial binding with elastomers is strong, while liquids usually have no adhesivity to bind to the elastomer. The high interfacial binding results in a high interfacial interaction and thus accounts for the phenomenon that gel fillers are more effective in enhancing dielectric performances than pure liquid fillers.…”
Section: The Influence Of Surfactants On Composites' Interfacial Comp...mentioning
confidence: 99%
“…For electrodes without adhesion, TENG also requires additional means of adhesion or curing to stabilize the structure, which greatly affects the efficiency of device preparation and use. 28 Therefore, the ideal flexible TENG should use both good elasticity (e.g., hydrogel or organogel) and compressive properties (e.g., conductive polymer composites) and at the same time have good environmental stability, high adhesion, and high conductivity electrodes.…”
Section: Introductionmentioning
confidence: 99%